Entrepreneurial Motivation from an Islamic Educational Perspective: Value Internalization and Character Formation among University Students - Diah Mutiara; Rony Edward Utama; Ichwan Rahmanu Widjaja; Saumi Sumanior (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2026)
The increasingly competitive labor market requires university students to develop entrepreneurial motivation that is grounded not only in economic objectives but also in moral and spiritual values. This study aims to analyze the entrepreneurial motivation of students at the Faculty of Islamic Studies, Universitas Muhammadiyah Jakarta (FAI UMJ), from the perspective of Islamic education and to examine the role of Islamic values-based entrepreneurship education in shaping students' entrepreneurial character. This research employed a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving FAI UMJ students and were analyzed descriptively. The findings indicate that students' entrepreneurial motivation is influenced by intrinsic and extrinsic factors, as well as the internalization of Islamic educational values. Principles such as honesty (ṣidq), trustworthiness (amanah), responsibility, hard work, discipline, and perseverance (ikhtiar) serve as the primary foundations for developing entrepreneurship oriented not only toward economic gain but also toward social benefit and divine blessing. Entrepreneurship education at FAI UMJ contributes positively to strengthening students' entrepreneurial knowledge, skills, and motivation through the integration of Islamic business ethics into the learning process. The novelty of this study lies in its integration of psychological, social, and religious dimensions within the framework of Islamic education, demonstrating that the internalization of Islamic values strengthens the character of ethical and socially responsible Muslim entrepreneurs. The study recommends strengthening Islamic values-based entrepreneurship curricula through practical training, business incubators, and sustainable entrepreneurial mentoring programs.